The Sleep of Neoliberal Reason: Denialism, Conspiracies and Storytelling on Crises through Ventajas de viajar en tren - Natalia Castro Picón (Humanities, 2022)
Do fictional figurations and their formal characteristics determine our relationship with the world? In a historical moment in which several crises overlap (economic, environmental, health), what cultural imaginaries circulate and with what consequences? One of the effects of this multilevel crisis, resulting from unrestrained neoliberalism, has been the rise of conspiracy theories of all kinds. The narrative of these conspiracies converges in many ways with the discursive structure of storytelling and fiction. Such narratives seem to serve as a model to interpret the present, overflowing the realm of representation. This article will explore commonalities between narrativity and conspiracy theories. In doing so, it will analyze Ventajas de viajar en tren, a novel by Antonio Orejudo and subsequent film adaptation Aritz Moreno. The story consists of a formal exploration of creating writing from a plot that addresses issues, such as conspiracy and mental health. I propose to invert this scheme to analyze how conspiracy theory operates as an act of discursive creation and what effects it has on our experience of the present and our relationship with the present and future in social, political and cultural terms.